Cardiac tumor in the left ventricular outflow tract: atypical presentation of calcified amorphous tumor. Issue 5 (18th May 2022) - Endo, Toyokazu; Lei, Kachon; Ahsan, Chowdhury
Abstract: Calcified amorphous tumor (CAT) of the heart is a rare nonneoplastic tumor. A 71-year-old woman presented with a mobile mass within the left ventricular outflow tract during her elective transthoracic echocardiogram. The patient exhibited no symptoms, and intraoperative findings showed the mass originating from the anterior leaflet of the mitral valve. Transthoracic and transesophageal echo failed to diagnose and localize the origin of the tumor. The tumor origin is unclear, but CAT of the mitral valve may be associated with mitral annular calcification. Surgical excision of the mass definitively diagnoses the tumor and reduces the risk of embolization.